2009
DOI: 10.1007/s11165-009-9140-2
|View full text |Cite
|
Sign up to set email alerts
|

From Young Children’s Ideas about Germs to Ideas Shaping a Learning Environment

Abstract: This paper is concerned with highlighting young children's ideas about the nature, location and appearance of germs, as well as their reasoning strands about germs' ontological category and biological functions. Moreover, it is concerned with exploring how all these could be taken into account for shaping a potentially fruitful learning environment. Conducting individual, semi-structured interviews with 35 preschoolers (age 4.5-5.5) of public kindergartens in the broader area of Patras, we attempted to trace t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…A first finding concerns the cognitive readiness of the children when they approach natural phenomena and concepts. As long as we agree that the cognitive development of the children is also important within the framework of preschool education institutions, from an educational point of view there is still an important issue not dealt with herein but already supported by other researches, namely the development of relevant science learning activities corresponding with both the research results and the limits of the actual work framework in the kindergarten (Resta-Schweitzer and Weil-Barais 2007; Kampeza and Ravanis 2009;Ergazaki, Saltapida, and Zogza 2010;Papandreou and Terzi 2011).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A first finding concerns the cognitive readiness of the children when they approach natural phenomena and concepts. As long as we agree that the cognitive development of the children is also important within the framework of preschool education institutions, from an educational point of view there is still an important issue not dealt with herein but already supported by other researches, namely the development of relevant science learning activities corresponding with both the research results and the limits of the actual work framework in the kindergarten (Resta-Schweitzer and Weil-Barais 2007; Kampeza and Ravanis 2009;Ergazaki, Saltapida, and Zogza 2010;Papandreou and Terzi 2011).…”
Section: Discussionmentioning
confidence: 86%
“…Thus, the use of different theoretical background, methods and pedagogical practices has shown that young children can approach systematically the natural world and construct in their thinking pre-concepts compatible with those of natural sciences, in several cognitive learning fields of natural sciences, such as biological phenomena (Zogza and Papamichael 2000;Christidou and Hatzinikita 2006;Ergazaki, Saltapida, and Zogza 2010), optical phenomena (Resta-Schweitzer and Weil-Barais 2007; Gallegos-Cázares, Flores-Camacho, and Calderón-Canales 2008; Ravanis 2010), astronomical phenomena (Kampeza 2006;Papandreou and Terzi 2011), properties of matter (Ravanis, Koliopoulos and Hadzigeorgiou 2004;Hatzinikita 2006;Vellopoulou and Ravanis 2010) electric and magnetic phenomena (Tsatsaroni, Ravanis, and Falaga 2003;Papadopoulou and Poimenidou 2008).…”
mentioning
confidence: 99%
“…These early-childhood misconceptions about microbes are not just restricted to their morphology or size, but also extend to their role in nature. Many studies in classrooms have shown that for children of all ages, microbes are exclusively associated with diseases and deficiencies in hygiene ( 10 , 19 , 27 ). This seems reasonable and reflects the history of microbiology guided by practical problems like health issues and food spoilage.…”
Section: Primary and Secondary School: Explore Your Microbiomementioning
confidence: 99%
“…Interestingly, although students acknowledge that germs are everywhere ( 27 ), they hold an incomplete picture of the interrelationships between macro- and microorganisms. For example, young students consider microbes as a strictly human problem, rather than seeing microorganisms as one of many organisms in the ecosystem, or as pathogens or symbionts for other organisms ( 19 , 27 ). In general, students think of humans as the center of the ecosystem rather than one member interdependent with other organisms such as microbes ( 26 , 40 ).…”
Section: Primary and Secondary School: Explore Your Microbiomementioning
confidence: 99%
“…From this perspective, children may be inclined to believe that learning-especially that which is related to lexical and semantic gains-is associated with stuttering. Second, children's belief that stuttering comes from germs is possibly linked to their knowledge that germs threaten one's physical well being (Ergazaki, Saltapida, & Zogza, 2010). Preschool Messages such as these may cause children to associate germs with all undesirable conditions.…”
Section: Stuttering Attitudes Of Nonstuttering Preschool Childrenmentioning
confidence: 99%